PENGARUH UNDANG – UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK TERHADAP GURU DALAM MENDIDIK SISWA - Mardia Pulungan (Bajang Institute, 2024)
This study aims to determine the effect of Law Number 23 of 2002 concerning child protection on teachers in educating. The research approach used is quantitative descriptive research. The research instruments used in this study are questionnaires and documentation. The number of respondents is 20 people using saturated sampling techniques (reasoning). Based on this, the sample criteria in this study are teachers of SMA Negeri 3 Panyabungan. The data that has been collected will then be analyzed by Structural Equation Modeling (SEM) based on the variant, namely Partial Square (PLS) with the help of the SmartPLS 3.0 program. Based on the results of the study, it was found that there is an effect of Law Number 23 of 2002 concerning child protection on teachers in educating, where the results of the path test showed that the calculated t is greater than the t table of 4,697 <1,724. Thus, it can be understood that teachers who respect and understand the law on child protection will demand teachers to be more creative in delivering lessons and more creative in giving sanctions